Establishment of serum protein pattern for screening colorectal cancer using SELDI-TOF-MS - Zheng, G.X.; Wang, C.X.; Qu, X.; Deng, X.M.; Deng, B.P.; Zhang, J. (Інститут експериментальної патології, онкології і радіобіології ім. Р.Є. Кавецького НАН України, 2006)
Aim: The purpose of this study is to develop a proteomic pattern for distinguishing individuals with colorectal cancer from healthy controls and monitoring micrometastasis using SELDI-TOF-MS. Methods: A training set consisting of 63 patients with colorectal cancer, 20 patients with benign colorectal diseases and 26 healthy volunteers was used to develop a proteomic model that discriminated colorectal cancer effectively. The sensitivity and specificity of this model was validated by an independent test set. To explore serum proteins changed after operation, the protein profiles of 31 postoperative patients were compared with those of preoperative patients. We also analyzed protein profiles of patients with and without metastasis to monitor micrometastasis. Results: Our study yielded a four-peak model (m/z: 3191.5, 3262.9, 3396.3 and 5334.4) that discriminated cancer from non-cancer samples with sensitivity of 90.3% and specificity of 95.7%. This model was validated in the test set with sensitivity of 87.5% and specificity of 93.8% which was significantly better than the combination use of CEA, CA199 and CA242 (sensitivity 62.4%) for early detection of colorectal cancer. Two peaks (m/z: 2753.8 and 4172.4) were found down-regulated in postoperative samples comparing with preoperative samples. We also detected two proteins (m/z: 9184.4 and 9340.9) that can discriminate patients with primary colorectal cancer from metastatic colorectal cancer. Conclusions: The four-peak model and two peaks (m/z: 2753.8 and 4172.4) detected in this study have the potential for assistance in diagnostics and therapeutic strategies in colorectal cancer and the two proteins (m/z: 9184.4 and 9340.9) were effective biomarkers for monitoring micrometastasis. Цель: исследование белкового профиля сыворотки крови больных колоректальным раком и здоровых доноров методом SELDI-TOF-MS для диагностики заболевания и мониторинга микрометастазов. Методы: методом SELDI-TOF-MS исследованы сыворотки крови 63 больных колоректальным раком, 20 больных с доброкачественными новообразованиями прямой кишки и 26 — здоровых доноров. Проведено сравнение профилей белков сыворотки крови 31 больного до и после хирургического вмешательства, а также больных с метастазами или без таковых. Результаты: получена 4-пиковая модель (m/z: 3191,5; 3262,9; 3396,3 и 5334,4), позволяющая отличить опухолевые образцы от неопухолевых с чувствительностью 90,3% и специфичностью 95,7%. Такая модель проверена в тест-системе с чувствительностью 87,5% и специфичностью 93,8%, что является лучшим результатом, чем комбинированное применение CEA, CA199 и CA242 (чувствительность 62,4%) для раннего выявления колоректального рака. Выявлено снижение интенсивности двух пиков (m/z: 2753,8 и 4172,4) при сравнении образцов до и после проведения операции, и идентифицированы два белка (m/z: 9184,4 и 9340,9), позволяющие выявлять больных колоректальным раком с метастазами. Выводы: полученная мод